Health Status After Cancer: Does It Matter Which Hospital You Belong To? - Hægeland Torbjørn; Fiva Jon H; Rønning Marte (BMC, 2010)
Abstract Background Survival rates are widely used to compare the quality of cancer care. However, the extent to which cancer survivors regain full physical or cognitive functioning is not captured by this statistic. To address this concern we introduce post-diagnosis employment as a supplemental measure of the quality of cancer care. Methods This study is based on individual level data from the Norwegian Cancer Registry (n = 46,720) linked with data on labor market outcomes and socioeconomic status from Statistics Norway. We study variation across Norwegian hospital catchment areas (n = 55) with respect to survival and employment five years after cancer diagnosis. To handle the selection problem, we exploit the fact that cancer patients in Norway (until 2001) have been allocated to local hospitals based on their place of residence. Results We document substantial differences across catchment areas with respect to patients' post-diagnosis employment rates. Conventional quality indicators based on survival rates indicate smaller differences. The two sets of indicators are only moderately correlated. Conclusions This analysis shows that indicators based on survival and post-diagnosis employment may capture different parts of the health status distribution, and that using only one of them to capture quality of care may be insufficient.